The Effectiveness of Ethanol Extract Gel of Cumin Leaves (Plectranthus Amboinicus) toward White Male Rat (Rattus Novergicus) - Alyidrus, Rugayyah; Alydrus, Nur Laela; Wahyuni, Wahyuni; Awaluddin, Nurhikma; Tangden, Nopianti (Jurnal EduHealth, 2022)
The leavers of white cumin (Plectranthus amboinicus) are a species of the family. Lamiaceae, previously known as Coleus amboinicus, contains quertesin compounds that are effective in healing wounds. The purpose of this study was to determine the extract of the leaves of white cumin (Plecranthus amboinicus) can be formulated for gel readiness and can affect the healing of cuts in white male rats (Rattus novergicus). The research method was laboratory experimental with the One Group Pretest- posttest research design. The leaves of white cumin (Plectranthus amboinicus) were extracted using 96% ethanol by maceration process and made into a gel form with a concentration of 3%, 5 %, and 7%. Evaluation of the physical and chemical stability of the gel before and after the cycling test for 6 cycles. This study used 15 male white rats divided into 5 groups, each group consisting of 3 and wounded with a depth of 2 cm and a length of 3 cm. the first male white rats were given a gel concentration of 3 %, the second 5%, the third 7 %, the fourth was given a gel without extract (negative control) and fifth was given 10 of octenilin gel (positive control). The incision length was measured on day 1,3,6,9,11,13 then data analysis used the ANOVA and SPSS 22 version. The results showed that leavers of white cumin (Plectranthus amboinicus) extract was p˂ 0,05, so there was a significant difference between each treatment. It can be concluded that gel readiness can be formulated and can affect wound healing in white male rats (Rattus novergicus).